TELEMETRI SUHU DAN GAS BERBASIS MIKROKONTROLER ATMEGA 16 - , MUTIARA VIDYASANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Telemetry temperature and gas provide ease in measuring distance, with monitoring from a safe place allow. Telemetry temperature and gas usually applied to volcano monitoring, monitoring of the steel melting, weather monitoring does not allow humans to perform measurements directly in close proximity. Additionally telemetry systems are often used in the space program to measure the surface temperature and the amount of gas on a planet, so the weather conditions on the planet can be estimated. Shipping information on telemetry can be done wireline and wireless. Information delivery technique is one that determines the reliability of telemetry system, especially if done in wireless information delivery. In this final project designed a telemetry temperature and gas system delivery using wireless data communication at a frequency of 2.4 GHz. 2.4 GHz frequency selected in this design is a ZigBee/XBee-Pro RF module that uses the IEEE 802.15.4 standard protocol. Using LM 35 temperature sensor and carbon monoxide measured by using gas sensor MQ-9. As the data processing center used microcontroller AVR ATMega 16.